ANALISIS SIFAT TERMAL KOMPOSIT LIMBAH MASKER BERPENGUAT SERAT BAMBU - Hana Nadia Ekawardani; Indah Widiastuti; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
This study aims to analyze differences in thermal properties, including thermal stability and the change in melting temperature (Tm) on variations in the mass fraction of fiber in mPP/bamboo fiber composite materials. Disposable face mask waste or mask polypropylene (mPP) is used as a polymer matrix and bamboo (Dendrocalamus asper) fiber as a composite reinforcement. The method used in this research is experimental. Variations in the mass fraction of bamboo fiber used were 0%, 4%, 8%, and 12%. Size of the bamboo fiber used is 5 mesh and has been treated with 5% NaOH alkali for 2 hours. The composite manufacture consists of two stages, namely the manufacture of mPP/bamboo fiber fragments by melting mask waste that has been mixed with bamboo fiber using an oven at 180°C for 2 hours. In the second stage, the mPP/bamboo fiber fragments were processed using an extruder machine with a processing temperature of 150°C and a screw speed of 25 rpm. Composite specimens measuring 2 x 2 x 2 mm with a weight of 1 to 10 mg were tested by TGA and DSC using a temperature of 25 to 900°C with a heating speed of 10°C/min in an oxygen atmosphere. The results of the thermogravimetry analysis (TGA) test showed that the neat mask polypropylene (mPP) without bamboo fiber reinforcement had the best thermal stability compared to other fiber mass fractions. The results of the differential scanning calorimetry (DSC) test showed that the mPP/0% bamboo fiber had the best melting temperature (Tm) at a temperature of 156.16˚C compared to other fiber mass fractions in the temperature range of 155°C to 156°C.